Modelling of Damping Properties of Articular Cartilage During Impact Load - KLEKIEL, Tomasz; WODZISŁAWSKI, Jarosław; BĘDZIŃSKI, Romuald (Engineering Transactions, 2017)
The paper presents some details about difficulties in modelling of articular cartilage. The most useful method to simulate a mechanism of tissue deformation during load is Finite Element Method (FEM). In this paper the authors present an approach of modelling a damping phenomenon in articular cartilage of an ankle joint. The damping property was modelled and analysed with an assumption that the reaction force is different suitable to change of a dynamic load. The model of lower extremity consists of three main bones: tibia, fibula and talus. The force acting on the model was generated from displacement of the talus according to the main biomechanical axis of a leg. The results present the role of an articular cartilage in distribution of energy inside the lower extremity. The analysis was carried out according to three main aspects: the reaction force in a support, the influence contact on the energy dissipation and the role of cartilage thickness in transmission of energy by the tibiotalar joint.